(untitled) (The International Journal for Scientific Research, 2026)
Environmental pollution is among the most critical contemporary challenges facing human societies due to its direct and indirect impacts on human health and the sustainability of urban ecosystems, particularly riverine environments, which constitute a fundamental element in shaping cities and their functional and spatial structures. This study addresses the problem of declining environmental and urban performance of riverfronts as a result of increasing urban pressures and the insufficient integration of environmental assessment tools into planning and architectural design processes. The study adopts a comprehensive analytical methodology, whereby the study area was divided into six environmental zones, each characterized by one or more environmental problems directly related to watercourses and their surrounding urban fabrics. These issues were subjected to integrated analysis within the framework of Strategic Environmental Assessment (SEA). The research examined the causes and impacts of environmental problems, the locations of pollution sources, their spatial extent, and the shared environmental interactions among different zones, in addition to identifying pollution levels and their effects on the environmental and urban performance of riverfronts. To achieve these objectives, a set of environmental assessment tools was employed, including the direct method, checklists, the Leopold Matrix, interaction matrices, and the Safir Matrix, alongside the use of Geographic Information Systems (GIS) and Google Maps to accurately identify problem locations and spatial extents. Integrating the outcomes of these analytical tools enabled the identification of the most influential environmental issues affecting the river system and adjacent urban riverfronts, particularly water pollution, water scarcity, and air quality deterioration in river-adjacent areas. Accordingly, the study proposes a set of sustainable planning and design solutions and alternatives to mitigate these problems or reduce their impacts, thereby supporting the effective integration of environmental considerations into urban planning and architectural riverfront design in Al-Siniyah City.